Rapid and Persistent Delivery of Antigen by Lymph Node Targeting PRINT Nanoparticle Vaccine Carrier To Promote Humoral Immunity - Mueller, Sarah N. (Mol Pharm, 2015)
[Image: see text] Nanoparticle delivery of subunit vaccines may increase vaccine efficacy, leading to a wide variety of safe and effective vaccines beyond those available through dosing inactivated or live, attenuated whole pathogens. Here we present a versatile vaccine delivery platform based on PRINT hydrogels made of biocompatible hydroxy-poly(ethylene glycol) (PEG) that is able to activate the complement system by the alternative pathway. These lymph node targeting nanoparticles (NPs) promote the immunogenicity of a model antigen, ovalbumin, showing comparable adjuvant effect to alum. We demonstrate that an antigen-specific humoral response is correlated with antigen delivery to the draining lymph nodes, in particular, B cell rich regions of the lymph nodes. 80 × 180 nm cylindrical NPs were able to sustain prolonged antigen presentation to antigen presenting cells (APCs) and elicit a stronger immune response than nondraining 1 × 1 μm NPs or rapidly clearing soluble antigen. The 80 × 180 nm NPs also show high levels of uptake by key APCs and efficiently stimulate CD4(+) helper T cell proliferation in vivo, further promoting antibody production. These features together produce a significant humoral immune response, superior to that produced by free antigen alone. The simplicity of the chemistries used in antigen conjugation to PRINT NPs confers versatility to this antigen delivery platform, allowing for potential application to many infectious diseases.